On the Role of Space, Place, and Social Networks in Social Participation - Gil Viry; Christoph van Dülmen; Marion Maisonobe; Andreas Klärner (Social Inclusion, 2022)
Recent literature recognises the importance of situating social networks in spatial contexts to better understand how space, place, and social networks interact and are co‐constituted. Despite this call, the mainstream literature in social network analysis pays relatively little attention to spatial dimensions of social networks and remains largely disconnected from the vast body of research on spatial networks in geography and cognate fields. This thematic issue is one step towards advancing this research agenda by examining how such an approach relates to issues of social inclusion and social participation. It includes a selection of studies that focus on the relation between space and social networks across a wide variety of research fields and contexts. Contributions use original, often mixed‐method approaches and multiple perspectives for capturing the role of space and people’s experience of place in network formation through physical, cultural, and geographical dimensions. We conclude this editorial by briefly suggesting areas for future research.